Iron, hepcidin, and microcytosis in canine hepatocellular carcinoma - Polak, Klaudia Zofia, author; Olver, Christine, advisor; Avery, Anne, committee member; Santangelo, Kelly, committee member; Shropshire, Sarah, committee member (Colorado State University. Libraries, 2021)
Hepatocellular carcinoma (HCC) is the most common primary liver tumor found in dogs. There is evidence that iron dysregulation is associated with HCC pathogenesis in both humans and dogs. Anemia and thrombocytosis were common hematologic abnormalities detected in about half of dogs with massive HCC, and microcytosis was present in approximately 31% of dogs in one study. Additionally, humans with hereditary hemochromatosis have an increased risk of HCC. The liver is the major organ site for iron storage and metabolism containing numerous iron regulatory proteins which may play an important role in canine HCC. Since microcytosis is associated with iron restricted erythropoiesis, our first objective was to determine whether neoplastic hepatocytes exhibit differential expression of iron regulatory genes as well as hepatic iron stores in normocytic versus microcytic HCC cases in an initial pilot study. Next, we aimed to quantify and compare expressions of a larger set of iron regulatory and human HCC-related genes among canine HCC tumor tissue, adjacent peritumoral liver tissue, non-specific reactive hepatitis liver tissue from non-HCC dogs, and normal liver tissue, as well as to quantify and compare estimated hepatic iron stores. We hypothesized that canine HCC tumor tissue exhibits iron overloading and higher expression of hepcidin and its upstream regulators (IL-6 and BMP6), which would promote intracellular iron availability for neoplastic hepatocyte proliferation. We also hypothesized that microcytic HCC cases would exhibit higher expression levels of hepcidin in tumor tissue compared to tumors from normocytic dogs. Additionally, we explored associations between clinical parameters and RNA levels of iron regulatory genes as well as estimated hepatocellular iron stores in both HCC tumor and the adjacent, peritumoral tissues. We expected to find gene expression patterns in canine HCC tumor tissue related to abnormal regulation of iron metabolism and other pathways similar to what has been described in human malignancies. Cases were selected from a database search for canine HCC and included if complete pre-operative blood work was available and there was adequate formalin-fixed paraffin-embedded (FFPE) tissue for RNA isolation for all cases. Hematologic and clinical parameters were recorded and used for correlation studies. All liver sections were reviewed by a board-certified veterinary anatomic pathologist. RNA was isolated from FFPE blocks and NanoString nCounter platform was used to quantify RNA counts for selected genes. Sections were stained with Perls Prussian Blue stain and hepatocytic iron stores were estimated using NIS-Elements software. Contrary to our hypotheses, all canine HCC tumors had markedly decreased expression of hepcidin (HAMP) and depletion of hepatocellular iron stores. Other iron-related genes down-regulated in canine HCC tumor tissue included TfR2 (an upstream regulator of hepcidin), STEAP2, LTF, HMOX1, CYBRD1and SFXN5. Tumor tissue overexpressed TfR1, STEAP3, and LCN2. No significant differences in RNA levels or iron stores were found between tumors of microcytic and normocytic HCC cases, but the adjacent peritumoral tissue was markedly iron loaded and exhibited negative correlation between hepcidin RNA levels and mean cell volume (MCV) as well as serum iron. Microcytic HCC cases were associated with noteworthy clinical findings such as increased ALT, lower HCT and serum iron, and histologically more poorly differentiated tumors. Differential expression of genes involved in Wnt signaling and ferroptosis was observed in canine HCC tumor versus the adjacent peritumoral liver tissue.
Keywords: hepcidin; microcytosis; STEAP3; iron; hepatocellular carcinoma; STEAP2